ANALISIS PERMINTAAN KREDIT MODAL USAHA PADA BANK PEMERINTAH DI SUMATERA UTARA - Putri Sari Silaban (Quantitative Economics Journal, 2012)
This research aims to analyze the influence of GDP, interest rate, CPI and the amount of deposits to the credit demand of venture capital to the state bank in North Sumatra simultaneously and partially. The data used are secondary data sourced from North Sumatra Bank of Indonesia variables namely GDP, interest rate, CPI and the number of deposit and loan capital of North Sumatra Province, on a quarterly basis from 2003 till , 2011. Data analysis was performed using OLS (Ordinary Least Square) with multiple linear regression models estimated with the help of the program Eviews 5.1. The results of this research can be concluded that simultaneous co-GDP variables constant change, the consumer price index, interest rate, and the amount of deposits significantly affect credit demand in the capital of North Sumatra Province. Furthermore, partially concluded that variables GDP, and the amount of deposits a positive effect on demand for capital loans, while the CPI and the variable mortgage interest rates negatively affect credit demand in the capital of North Sumatra Province. The results also showed that the most dominant variable effect on credit demand in the province of North Sumatra capital is the amount of deposits.